Structural Transformation versus Environmental Quality: The Experience of the Low-income Countries in Sub Saharan Africa - Awad, Atif (International Journal of Energy Economics and Policy, 2021)
Structural transformation has been recognized as a critical mechanism for improving living standards for developing countries in Africa. However, the growing evidence indicates that such change is associated with considerable damage to the environment quality and, hence, challenging sustainable development. The present study investigates industrialization’s influence on the environment quality for 20 low-income countries in Sub-Saharan Africa during 1980-2018. We employed two measurements for environmental quality, which are CO2 and nitrous dioxide emissions. Likewise, the study applied the Fully modified OLS and the Dynamic OLS as the most modern and suitable techniques related to the panel data analysis. Overall, the FMOL and DOLS results show that industrialization has an insignificant influence on environmental quality. The results also show that these countries’ population size is the main driver for environmental quality changes. This finding implies that these countries should continue in their current efforts regarding promoting the industrial sector without wondering about sustainable development. Keywords: EKC; industrialization; Low-income countries; FMOL; DOLS. JEL Classifications: Q560, Q580, O140, O550 DOI: https://doi.org/10.32479/ijeep.11516